2006
DOI: 10.1111/j.1440-1843.2006.00874.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 87 patients with Löfgren’s syndrome and the pattern of seasonality of subacute sarcoidosis

Abstract: In this study, there were differences in the amplitude of the seasonal variation by age and by gender. Well-designed prospective studies are required to better understand the importance of the findings we respect to the pathogenesis of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…No studies have assessed the seasonality of Tuberculin results; however, patients with sarcoidosis are usually anergic to Tuberculin due to their poor immunity. The current study has shown that the seasonal variation in the onset of sarcoidosis symptoms in the subset of patients who were Tuberculin anergic, was comparable with that seen in the total sarcoid patient cohort 6 . These observations are important, particularly for countries in which tuberculosis is endemic and where BCG vaccination is routine, as Tuberculin anergy will parallel the activation of sarcoidosis and its seasonal variation.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…No studies have assessed the seasonality of Tuberculin results; however, patients with sarcoidosis are usually anergic to Tuberculin due to their poor immunity. The current study has shown that the seasonal variation in the onset of sarcoidosis symptoms in the subset of patients who were Tuberculin anergic, was comparable with that seen in the total sarcoid patient cohort 6 . These observations are important, particularly for countries in which tuberculosis is endemic and where BCG vaccination is routine, as Tuberculin anergy will parallel the activation of sarcoidosis and its seasonal variation.…”
Section: Discussionsupporting
confidence: 73%
“…Both host and environmental factors may play important roles in the aetiopathogenesis of sarcoidosis’ 2 . Seasonal variation studies are important if infective agents are involved or if a specific time period needs to be targeted for investigation of the disease 3–6 . This study evaluated the seasonal variation in the onset of symptoms, Tuberculin anergy and Kveim positive reaction in symptomatic patients with sarcoidosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in agreement with previous studies studying seasonal variability of sarcoidosis. [ 16 24 25 26 ] The increased incidence of infections and pleural effusions can be explained by the impact of the rains in the Indian subcontinent. [ 27 28 29 ] A higher incidence of tuberculosis was seen in spring and summer months in a review of several studies similar to our experience.…”
Section: Discussionmentioning
confidence: 99%
“…The syndrome is rare between young children and teenagers and elder people over the age of 70 [13]. Females are three times more likely to have Löfgren's syndrome than males [14], significantly frequent in springtime compared to wintertime [15]. Past studies suggest, that environmental, occupational factors, contacts with dust or chemicals may trigger the disease [16].…”
mentioning
confidence: 99%